Social media as an instrument of activism for feminist university students in Mexico: the cases of MOFFyL and Uni Unida - Mandujano Salazar, Yunuen Ysela (Routledge, 2021)
In this chapter, we analyze the use of social media in the development of two Mexican feminist university collectives—Universidad Nacional Autónoma de México’s MOFFyL and Universidad Autónoma de Ciudad Juárez’s Uni Unida—focusing on the role of such media as means of online and offline activism. Relying on digital and regular ethnography, as well as on documental research, we rebuild the history of the collectives and the role of digital technologies in their formation and consolidation. The results show that for young Mexican people, social media is one of their main channels of communication, and to make visible, particularly among university students, it is Facebook the preferred social media. Also, originally a medium of communication, eventually the Facebook pages became the main source of political discourse during the student strikes and/or the activism platform. Thus, we demonstrate that contrary to the term slacktivism, digital activism has become the key to the future success of social movements.